2007
DOI: 10.1371/journal.pone.0000954
|View full text |Cite
|
Sign up to set email alerts
|

Signaling of Human Frizzled Receptors to the Mating Pathway in Yeast

Abstract: Frizzled receptors have seven membrane-spanning helices and are considered as atypical G protein-coupled receptors (GPCRs). The mating response of the yeast Saccharomyces cerevisiae is mediated by a GPCR signaling system and this model organism has been used extensively in the past to study mammalian GPCR function. We show here that human Frizzled receptors (Fz1 and Fz2) can be properly targeted to the yeast plasma membrane, and that they stimulate the yeast mating pathway in the absence of added Wnt ligands, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…We have shown that Frizzled receptors co-expressed with chimeric G proteins can activate the yeast MAPK pathway, thus confirming Frizzled as a GPCR. These results confirm those obtained by another group that expressed human Frizzled receptors 1 and 2 and observed activation of the yeast MAPK pathway through the yeast G proteins [42]. Our study extends this work by showing that there is specificity in the interaction between Frizzleds and chimeric G proteins, with Frz1, Frz2, Frz6 and Frz7 preferentially interacting with Gpa1/Gα s over Gpa1/Gα i or Gpa1/Gα q .…”
Section: Discussionsupporting
confidence: 92%
“…We have shown that Frizzled receptors co-expressed with chimeric G proteins can activate the yeast MAPK pathway, thus confirming Frizzled as a GPCR. These results confirm those obtained by another group that expressed human Frizzled receptors 1 and 2 and observed activation of the yeast MAPK pathway through the yeast G proteins [42]. Our study extends this work by showing that there is specificity in the interaction between Frizzleds and chimeric G proteins, with Frz1, Frz2, Frz6 and Frz7 preferentially interacting with Gpa1/Gα s over Gpa1/Gα i or Gpa1/Gα q .…”
Section: Discussionsupporting
confidence: 92%
“…However, in recent years, studies on GSK-3β and Wnt/β-catenin signaling in tumor cells suggested that inhibition of GSK-3β could both inhibit or promote Wnt/β-catenin signaling [31.] GSK-3β has two ways to modulate β-catenin, revealing that GSK-3β can negatively regulate Wnt/β-catenin signaling through degradation of β-catenin (the traditional view), but can also positively control expression of β-catenin by an even more complex regulatory mechanism [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Human Frizzleds equipped with the N-terminal signal sequence from yeast 7TM STE2 receptor are capable of recruiting the yeast mating pathway, which requires the activation of a heterotrimeric G protein (Dirnberger and Seuwen, 2007). Even though this artificial system does not prove that FZDs can do the same in mammalian cells, it is indeed a strong indication.…”
Section: A Pros and Cons Of G Protein Couplingmentioning
confidence: 95%